Problematika Manajemen Pendidik dan Tenaga Kependidikan Lembaga Pendidikan Islam di Indonesia - Hadit Pratama; Muhammad Abel Afif; Gusmaneli Gusmaneli (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Educator management has a very important role in knowing the level of success of a learning system implemented by educators. With good management, you can develop a learning system so that it will affect the quality of learning carried out by educators. Educator management is tasked with planning, managing and organizing educators and education staff so that they are able to manage all aspects of education well. When carrying out management, you must pay attention to the basic principles of management and procedures in carrying out management, so that this management can run according to its function. Management is an effort to manage educators from the moment they enter until they leave (retire) to determine the effectiveness and efficiency of learning activities. Therefore, the role of management is very important in improving the quality of educators in Indonesia. This research uses a literature review method by searching for related sources.